'No better story to tell': framing anti-colonialism in the aid exposé documentary. Issue 3 (3rd July 2021) - O'Loughlin, Liam
ABSTRACT: This essay identifies the emergence of the aid exposé documentary, a set of contemporary films that overtly challenge the moral benevolence and economic function of humanitarian and development aid. These films are situated within a broader twenty-first century public critique of aid but constitute an aesthetic divergence from the images of suffering found in the long, intertwined history of visual media and humanitarianism. Against that backdrop, aid exposé films frame themselves as anti-colonial correctives to aid's structural exclusion, elevating conflicting notions of entrepreneurialism and the process of popular sovereignty. The essay argues that the aid exposé is a malleable genre, mobilised to both consolidate and challenge the conditions of neoliberalism, and thus marks an important popularisation of the ongoing 'aid debate'.